2004
DOI: 10.1093/humrep/deh533
|View full text |Cite
|
Sign up to set email alerts
|

Blood lymphocyte chimerism associated with IVF and monochorionic dizygous twinning: Case report

Abstract: We report on dizygotic (DZ) twins, conceived by IVF and ICSI with assisted hatching, who each had a mixture of 46,XX and 46,XY cells in blood lymphocytes. The female twin had mild genitalia abnormalities but further study revealed anatomically normal reproductive anatomy. Chromosome and fluorescence in situ hybridization studies of buccal, skin and ovarian tissue were normal, as were buccal tissue DNA studies. Fetal ultrasound and fetal membrane pathology were consistent with a monochorionic, diamniotic placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 15 publications
2
44
0
3
Order By: Relevance
“…DNA studies of skin fibroblasts showed pure dizygosity without evidence of chimerism. A similar twin pair was reported [Williams et al, 2004], conceived by IVF and intra-cytoplasmic sperm injection (ICSI) with assisted hatching and transfer of two embryos. The placenta was MC by ultrasound, confirmed by pathology.…”
Section: Article American Journal Of Medical Genetics Part C (Seminarmentioning
confidence: 98%
“…DNA studies of skin fibroblasts showed pure dizygosity without evidence of chimerism. A similar twin pair was reported [Williams et al, 2004], conceived by IVF and intra-cytoplasmic sperm injection (ICSI) with assisted hatching and transfer of two embryos. The placenta was MC by ultrasound, confirmed by pathology.…”
Section: Article American Journal Of Medical Genetics Part C (Seminarmentioning
confidence: 98%
“…As in our case, the majority of those described previously have occurred in the context of infertility treatment with ovarian stimulation and artificial insemination i.e. IVF or IVF + ICSI [3,6,8,9,[11][12][13][14]16]. Typically numerous embryos were transferred simultaneously.…”
mentioning
confidence: 51%
“…To date 15 cases of monochorionic, dizygotic twins with chimerism have been described [3][4][5][6][7][8][9][10][11][12][13][14]. Most of these cases were blood chimerisms due to twin-twin transfusion in the presence of a common placenta [3,[5][6][7][8][10][11][12][13]; in this case chromosomal analysis of mucosa or skin biopsy is consistent with phenotypic sex. In the current case FISH was carried out on urothelium from both twins.…”
mentioning
confidence: 78%
“…However, no MCDZTs with cellular chimerism involving cells other than blood cells have been reported in the literature to date. [2][3][4][5] Here we report a probable first case of MCDZTs with buccal cell chimerism.…”
mentioning
confidence: 78%
“…Although various tissues other than blood derived from MCDZTs have been investigated in previous studies, none of these tissues demonstrated chimerism. [1][2][3][4][5] Previous reports thus concluded that chimerism is confined to blood cells and that clinical consequences of chimerism in other tissues would be minimal.…”
Section: Discussionmentioning
confidence: 99%